2022
DOI: 10.3390/ijms23147919
|View full text |Cite
|
Sign up to set email alerts
|

Shape Transformations and Self-Assembly of Hairy Particles under Confinement

Abstract: Molecular dynamics simulations are used to investigate the behavior of polymer-tethered nanoparticles between two inert or attractive walls. The confinement in pores creates new possibilities for controlling the shape transformation of individual hairy particles and their self-organization. We introduce a minimalistic model of the system; only chain–wall interactions are assumed to be attractive, while the others are softly repulsive. We show how the shape of isolated particles can be controlled by changing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It was shown that adsorption of isotropic particles "on chains" caused reconfiguration of the tethered chains, leading to a variety of morphologies, including typical core-shell structures and octopus-like and corn-like structures [192]. The impact of the solid surface on the configurations of tethered polymers was also analyzed [194,195]. Furthermore, numerous studies have focused on the selfassembly of hairy particles in bulk systems, as these particles are promising building blocks for the production of novel nanocomposites [196][197][198].…”
Section: Individual Hairy Particles At Fluid-fluid Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that adsorption of isotropic particles "on chains" caused reconfiguration of the tethered chains, leading to a variety of morphologies, including typical core-shell structures and octopus-like and corn-like structures [192]. The impact of the solid surface on the configurations of tethered polymers was also analyzed [194,195]. Furthermore, numerous studies have focused on the selfassembly of hairy particles in bulk systems, as these particles are promising building blocks for the production of novel nanocomposites [196][197][198].…”
Section: Individual Hairy Particles At Fluid-fluid Interfacesmentioning
confidence: 99%
“…Figure 6 shows equilibrium configurations of Janus-like hairy particles at the liquid-liquid interface obtained from molecular dynamic simulations. The interface and the hairy particles were modelled according with procedures described in works [153,194,195]. Interactions between "atoms" are modeled by the shifted-force Jenard-Jones potentials.…”
Section: Individual Hairy Particles At Fluid-fluid Interfacesmentioning
confidence: 99%
“…We also introduce the following assumptions [26,27,44]: (i) interactions of the cores with the remaining "atoms" are purely repulsive, (ii) interactions between the same "atoms" are attractive (𝜀 * 𝑖𝑖 = 1). We consider the particles interacting (i) "symmetrically" and (ii) "asymmetrically" with both liquids.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of adsorption on solids depends on the size and shape of the particles. Therefore, changes in the shape of hairy particles on the solid surfaces and inside the pores were investigated [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Various self-assembled structures of NPs have been revealed by simulations [ 22 , 23 , 24 , 25 ] and experiments [ 26 ]. For example, Janus NPs—also known as patchy NPs—are representative modified NP systems that exhibit unprecedented unique self-assembled structures.…”
Section: Introductionmentioning
confidence: 99%